The Role of Cyber Counseling in Enhancing Emotional Regulation Among Generation Z College Students - Alifa S Rahmadhina (Publikasi Indonesia, 2026)
The rapid integration of digital communication technologies into higher education has transformed the delivery of psychological support services, positioning cyber counseling as an increasingly relevant intervention for Generation Z college students. As digital natives, Gen Z demonstrates strong engagement with technology-mediated communication, making online counseling platforms particularly compatible with their help-seeking preferences. At the same time, emotional regulation remains a critical psychological competency for navigating academic stress, interpersonal challenges, and digital-era psychosocial pressures. This study employed a quantitative cross-sectional survey design involving 327 undergraduate students aged 18–24 who had previously participated in cyber counseling services. Participants were selected using purposive sampling. Data were collected through validated self-report instruments measuring cyber counseling utilization and emotional regulation. Statistical analyses included descriptive statistics, reliability and validity testing, Pearson correlation analysis, and Structural Equation Modeling (SEM). The findings revealed that cyber counseling utilization was positively associated with emotional regulation (r = 0.61, p < .001). Structural model analysis indicated that cyber counseling significantly predicted emotional regulation (β = 0.58, p < .001), explaining 33.6% of the variance. Among cyber counseling dimensions, counselor responsiveness emerged as the strongest perceived factor, while privacy and security perception recorded comparatively lower evaluations. The results suggest that cyber counseling serves as an effective digitally mediated platform for enhancing emotional regulation among Generation Z college students. The study highlights the importance of relational quality, technological trust, and responsive counseling practices in optimizing digital mental health interventions within higher education contexts.